Remedial physical culture in complex physical rehabilitation after arthroscopic surgery about the ligament ruptures of knee joint - Без’язична [Olga Bezyazychnaya], Ольга Володимирівна (Slobozhanskyi Herald of Science and Sport, 2013)
The article deals with the major modern approaches to prescribing remedial physical culture in complex physical rehabilitation after arthroscopic surgery about the ligament ruptures of knee joint. An etiology, clinical symptoms and methods of treatment injuries of knee joint are characterized. Determined are the tasks, forms and means of remedial physical culture. The methodics of remedial gymnastics of fractures after arthroscopic surgery about the ligament rupture of knee joint with an account of the early postoperating, late postoperating and recovering periods of disease are defined in detail. The major approaches to prescribing of medical massage and physiotherapy are presented.